Reconstructive Challenges and Outcomes Following Radical Resection of Sinonasal Squamous Cell Carcinoma via Weber-Ferguson Approach: A Case Study - Ni Putu Deby Rathasari; I Gde Ardika Nuaba; I Ketut Suanda (HM Publisher, 2025)
Sinonasal squamous cell carcinoma (SCC) is an uncommon malignancy characterized by diagnostic delays and complex management. Advanced-stage disease often necessitates radical surgical resection, leading to significant anatomical defects and formidable reconstructive challenges. The Weber-Ferguson approach provides wide surgical exposure for extensive tumors but results in considerable midfacial defects requiring meticulous reconstruction to restore function and aesthetics. This case study details the reconstructive challenges and outcomes following total maxillectomy with this approach for an advanced sinonasal SCC. A 53-year-old male presented with a one-month history of right cheek pain and swelling, preceded by a year of right upper molar pain and progressive facial masses. Clinical and radiological evaluations revealed an extensive mass originating from the right maxillary sinus, destructing surrounding bony structures and involving regional lymph nodes. Biopsy confirmed poorly differentiated keratinizing squamous cell carcinoma. The patient underwent a right total maxillectomy via a Weber-Ferguson approach with Lynch modification, extended to involve the mandible, along with reconstruction. The final staging was T4aN3M0. Postoperatively, the patient experienced minor wound dehiscence, which was managed conservatively. He was planned for an obturator and adjuvant radiochemotherapy, but he declined further oncological treatment. Radical resection of advanced sinonasal SCC using the Weber-Ferguson approach, while oncologically necessary, presents substantial reconstructive dilemmas. Addressing these defects is crucial for functional rehabilitation, including speech, deglutition, and acceptable cosmesis. This case underscores the complexity of managing such extensive defects and the importance of a multidisciplinary approach, even when patients decline standard adjuvant therapies. The long-term prognosis in such cases remains guarded, particularly without adjuvant treatment.